2012
DOI: 10.1248/bpb.35.933
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Risk Factors Associated with Adverse Drug Reactions by Metformin in Type 2 Diabetes Mellitus

Abstract: Metformin is a drug to improve glycemic control by reducing insulin resistance and is currently considered to be one of the first-choice drugs for type 2 diabetes mellitus (T2DM). However, during metformin use, adverse drug reactions (ADRs) including gastrointestinal adverse events were frequently observed. Thus, in the present study, we investigated the incidence of ADRs induced by metformin and further analyzed risk factors for ADRs in Japanese patients with type 2 diabetes mellitus who initially administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 24 publications
1
43
1
6
Order By: Relevance
“…Stratified randomization was used to minimize the impact of imbalanced factor distribution, which might influence study outcomes. Previous reports indicated that individuals with different body weights tend to have different GI conditions and differences in tolerability to metformin; however, the reported effect of BMI on GI tolerability is inconsistent . It is well known that baseline HbA1c level is positively correlated with the magnitude of HbA1c reduction from baseline with any oral hypoglycaemia medication …”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…Stratified randomization was used to minimize the impact of imbalanced factor distribution, which might influence study outcomes. Previous reports indicated that individuals with different body weights tend to have different GI conditions and differences in tolerability to metformin; however, the reported effect of BMI on GI tolerability is inconsistent . It is well known that baseline HbA1c level is positively correlated with the magnitude of HbA1c reduction from baseline with any oral hypoglycaemia medication …”
Section: Methodssupporting
confidence: 92%
“…Previous reports indicated that individuals with different body weights tend to have different GI conditions and differences in tolerability to metformin; however, the reported effect of BMI on GI tolerability is inconsistent. 11,[19][20][21] It is well known that baseline HbA1c level is positively correlated with the magnitude of HbA1c reduction from baseline with any oral hypoglycaemia medication. 22 During the 16-week treatment period, metformin XR and IR were administered orally, with food, at a 500-mg/d starting dose.…”
Section: Treatmentmentioning
confidence: 99%
“…Due to robust evidence, current international guidelines recommend metformin as the only first-line oral anti-hyperglycaemic agent for patients with newly diagnosed T2DM (7,18). As gastrointestinal complications occur in more than 20% of the patients using metformin (19,20), other anti-hyperglycaemic agents are considered as substitutes for the initial pharmacological therapy for those with contraindications to metformin. In this study, repaglinide and metformin had similar effects on HbA1c, which was in accordance with previous studies (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…A daily oral dose of 2000–2500 mg/day is typically required for optimal effect8 and oral bioavailability is dose-dependent, with decreased bioavailability at higher doses, suggesting an active, saturable absorption process 9. Although severe adverse effects are rare, up to 30% of patients report gastrointestinal symptoms, including diarrhea, cramps, nausea, and vomiting, which can cause severe discomfort and lead to discontinuation of the drug 10. Therefore, finding strategies to reduce the dose of metformin required without compromising its efficacy is a useful approach for managing and reducing adverse events.…”
Section: Introductionmentioning
confidence: 99%